QUANTUM DOTS AS NEAR-INFRARED FLUORESCENT PROBES FOR REAL-TIME IN VIVO BIOIMAGING OF CANCER CELL METASTASIS - Oumar Traore; Binta Konate; Fatiata Diarra (Journal of Biomedical and Techno Nanomaterials, 2025)
Cancer metastasis is the primary cause of cancer-related mortality, yet its dynamic progression in living systems remains difficult to visualize due to limitations of existing imaging probes. Conventional fluorescent dyes used for in vivo bioimaging often suffer from poor photostability, limited brightness, and insufficient tissue penetration, restricting their ability to capture metastatic events in real time. This study aims to develop and evaluate near-infrared-emitting quantum dots as fluorescent probes for real-time in vivo bioimaging of cancer cell metastasis. An experimental nanobiotechnology approach was employed, involving the synthesis of near-infrared quantum dots, surface functionalization to enhance biocompatibility, physicochemical and optical characterization, and biological evaluation using metastatic cancer cell lines and small animal models. Optical analysis demonstrated high quantum yield, narrow emission bandwidth, and excellent photostability within the near-infrared window. In vitro assays confirmed high cell-labeling efficiency with minimal cytotoxicity, while in vivo imaging revealed sustained and high-contrast fluorescence signals that enabled continuous tracking of cancer cell migration and organ colonization. Ex vivo validation corroborated in vivo imaging findings. These results indicate that near-infrared quantum dots provide superior performance compared to conventional fluorescent probes for dynamic metastasis imaging. In conclusion, quantum dot–based near-infrared probes represent a powerful and versatile platform for real-time in vivo visualization of cancer metastasis, offering significant potential for advancing cancer research and diagnostic imaging.